The syntactic displacement in the poem entitled CHAKWA AL ASSIMI by Mohammed El Bachir AL IBRAHIMI - remmache, adel. (El Omda in Linguistics and Discourse Analysis, 2023)
This article deals with the phenomenon of syntactic displacement in the poem of CHAKWA AL ASSIMI by Mohammed El Bachir AL IBRAHIMI. This is an applied study in which I try to reveal the aesthetic effect achieved by compositional deviations through its multiple forms, such as submission, delay and omission, based on the descriptive approach accompanied by analysis as a procedural mechanism. The results of the most important of which are the realization of semantic transmission by these alterations, which are sublime linguistic structures and a pictorial style characterized by suggestive intensification and semantic synthesis from one position to another, by carrying the meanings of words from their original position to another meaning that stimulates the recipient and draws him to it.